Evaluation of Optimal Area Usage in Kastamonu City Center in terms of Landscape Planning - ÖZTÜRK, Sevgi; KALAYCI KADAK, Merve (Alinteri Zirai Bilimler Dergisi, 2020)
Nowadays, natural and cultural resources are being rapidly depleted. However, protection approaches that can be effective against this situation are not exhibited. Existing resources are at risk of extinction with to use incorrect of space. In order to be able to make the right resource use and planning decisions, it is necessary to determine the optimal area uses considering the ecological basis. The study was conducted at the border urban area of Kastamonu province. Natural and cultural resource values have been examined to determine area uses. In the first phase, the literature search is completed. Then field inventory studies were carried out. In the second phase; numerical suitability maps have been established for three different field types of agriculture, forest, settlement areas. Geographic Information Systems program, that ArcGIS 10.0 software, was used as a tool. Finally, the optimal fitness of the digitized areas has been determined. Potential resource values of Kastamonu city center, due to incorrect use of areas and lack of planning, was determined not adequately assessed. To prevent incorrect use of space; local governments are required to make area utilization decisions in a short time. Making the environmentally sensitive planning studies, to provide tourism within the protection-utilization balance of resources and it has been found that the promotion of the promotion is very economically important. It has been determined that there is misuse in the study where ecological conformities of existing natural and cultural resources are tested. It has been determined that resource values for these areas have deteriorated due to misuse. The reason behind all this is unconscious urbanization. It has been determined that sustainable resource use will not be possible due to this pressure.
Keywords: 11. Sustainability; 15. Life on land; 12. Responsible consumption